Effectiveness of Summons and Notifications Via Registered Letter in The Kuala Kapuas Religious Court - Imelda Yuliandari; Abdul Khair; Kamal Hasuna (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2024)
This Study motivated by existing calls and notifications the judge through letter recorded failure​ until to address party who has registered trial at the Religious Court via system e-court. Focus study How are this mechanism delivery calls and notifications through letters recorded at the Kuala Kapuas Religious Court and the obstacles faced Kuala Kapuas Religious Court in applying calls and notifications through letters recorded. The method used​ in the study This use type of study law empirical with an approach to social-legal research. Research data was collected with method observation, interviews, and documentation, and analyzed using Legal Certainty, Legal Change, and Legal Effectiveness theory. Research results show that: First, Mechanism delivery calls and notifications through letter registered at the Kuala Kapuas Religious Court is the bailiff calls the plaintiff through e-mail and the defendant through a letter recorded. Registered letter This be delivered through the post office. Obstacles encountered​ Kuala Kapuas Religious Court in applying calls and notifications through letters recorded in a way general is when the distance traveled is very long, and the costs To reach it No under cost incurred​ by party litigants, and letters recorded often slow until so that make delay quite a long trial.